"Inspiring" and configuring consumer experience in times of crisis: An analysis of the discursive practices of an Athenian shopping mall's promotional system. (November 2022) - Lallas, Dimitris; Drosos, Yorgos
This article focuses on the processes that the largest shopping mall in Athens has developed in order to produce meaning about itself as an institution of consumption, as well as the consumer experience and practices, and its visitors–consumers. From a poststructuralist perspective, we analyze the signifying articulations that the promotional discourse attempts, along with the linguistic and visual techniques which activate specific significations about this microcosm of consumption, the "fun" experience, fashion, beauty, shopping and entertainment practices, eating out, and the consumer subjectivity. The ultimate aim of this research is to point out the cultural role of such an institution with regard to the configuration of an order of discourse about consumption and the reproduction of the consumerist ethos during an economic crisis, as well as the possible effects that such a discourse might have on a wider cultural level.